Human TLR-7-, -8-, and -9-mediated induction of IFN-alpha/beta and -lambda Is IRAK-4 dependent and redundant for protective immunity to viruses. - Yang, K; Puel, A; Zhang, S; Eidenschenk, C; Ku, C; Casrouge, A; Picard, C; von Bernuth, H; Senechal, B; Plancoulaine, S; Al-Hajjar, S; Al-Ghonaium, A; et al. (2005)
Five TLRs are thought to play an important role in antiviral immunity, sensing viral products and inducing IFN-alpha/beta and -lambda. Surprisingly, patients with a defect of IRAK-4, a critical kinase downstream from TLRs, are resistant to common viruses. We show here that IFN-alpha/beta and -lambda induction via TLR-7, TLR-8, and TLR-9 was abolished in IRAK-4-deficient blood cells. In contrast, IFN-alpha/beta and -lambda were induced normally by TLR-3 and TLR-4 agonists. Moreover, IFN-beta and -lambda were normally induced by TLR-3 agonists and viruses in IRAK-4-deficient fibroblasts. We further show that IFN-alpha/beta and -lambda production in response to 9 of 11 viruses tested was normal or weakly affected in IRAK-4-deficient blood cells. Thus, IRAK-4-deficient patients may control viral infections by TLR-3- and TLR-4-dependent and/or TLR-independent production of IFNs. The TLR-7-, TLR-8-, and TLR-9-dependent induction of IFN-alpha/beta and -lambda is strictly IRAK-4 dependent and paradoxically redundant for protective immunity to most viruses in humans.